2021
DOI: 10.1038/s41598-021-87163-5
|View full text |Cite
|
Sign up to set email alerts
|

Time-lag of urinary and salivary cortisol response after a psychological stressor in bonobos (Pan paniscus)

Abstract: Cortisol is often measured as a marker for stress. Therefore, a profound validation of the time-lag between the stressor and the increase and peak in cortisol levels is needed. No study measured both the urinary and salivary cortisol time-lag after a psychological stressor. In this study, we used a frequent sampling study design to (1) describe the urinary and salivary cortisol pattern during a control day; and (2) characterize the induced excretion pattern of urinary and salivary cortisol after a psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 88 publications
1
25
0
Order By: Relevance
“…As the intercept of the curve is the constant with which cortisol levels decrease, and the decrease is assumed to be steady, the bias introduced in our data due to difference in the timing of sample collection should be relatively mild. For both, the estimates of SCI and SCS, a major concern would have been if the steep decline in cortisol levels associated with the awakening response [ 23 , 67 ] would have been included in our sample, which is not the case though. However, future studies should ideally keep sampling conditions constant across species to avoid potential difficulties in the interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the intercept of the curve is the constant with which cortisol levels decrease, and the decrease is assumed to be steady, the bias introduced in our data due to difference in the timing of sample collection should be relatively mild. For both, the estimates of SCI and SCS, a major concern would have been if the steep decline in cortisol levels associated with the awakening response [ 23 , 67 ] would have been included in our sample, which is not the case though. However, future studies should ideally keep sampling conditions constant across species to avoid potential difficulties in the interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
“…This approach means, however, that we did not include samples from the early morning or late afternoon as done in human studies of cortisol slopes [ 10 , 80 ]. Previous studies in chimpanzees [ 67 ], bonobos [ 23 ], and orangutans [ 52 ] have demonstrated that also in these species, there is a peak in salivary cortisol in early morning (depending a bit on when samples were taken 6 a.m. in chimpanzees, 8:30 in bonobos), followed by a steep decline until noon, and then followed by a slower decline between noon and 4 p.m. with nearly half of the level at 4 p.m. compared to noon [ 23 , 67 ]. This means in our study we only measured the slow decline during the afternoon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this significant association died out between MASQ and K10 scores when cortisol after exercise was incorporated into the model. Since cortisol levels were not assessed on Wednesday but Saturday (and during a downtime), this suggests a potential lag-time between negative affect and cortisol levels [ 40 ]. Taken together, it seems that the relationship between K10, MASQ, and cortisol levels before exercise is stronger on a peak day (Wednesday) compared with a weekend (Saturday).…”
Section: Discussionmentioning
confidence: 99%
“…The five-fold increase in cortisol that we observed in our study is an unusually strong physiological response. For comparison, captive bonobos exposed to an experimental stress test exhibited a two-fold increase in cortisol levels (Verspeek et al, 2021). A similar cortisol response occurs in group members in response to infant birth, but levels returned to normal within one day (Behringer et al, 2009).…”
Section: Discussionmentioning
confidence: 99%